2010
DOI: 10.1007/s11999-009-1131-0
|View full text |Cite
|
Sign up to set email alerts
|

Is MRI Adequate to Detect Lesions in Patients with Ankle Instability?

Abstract: Background Chondral lesions, peroneal tendon tears, and other disorders in patients with chronic ankle instability may not be detected by preoperative MRI. Also, MRI often is obtained and interpreted at the referring institution, leading to variability in reading. Questions/PurposesWe assessed the accuracy of the radiologists' and orthopaedic surgeon's reading of preoperative MRI for diagnosing ankle lesions in patients with ankle instability warranting surgery. Patients and Methods We retrospectively reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 25 publications
4
30
1
Order By: Relevance
“…We routinely use it to identify talar osteochondral lesions (OCLs) and then we can counsel patients as the treatment of these lesions often changes the post-operative protocol in addition to the surgical plan. MRI sensitivity for concomitant lesions is high, especially when evaluating for osteochondral lesions [41][42][43][44]. However, the utility in diagnosing symptomatic lateral ankle instability is limited because it is a static study.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…We routinely use it to identify talar osteochondral lesions (OCLs) and then we can counsel patients as the treatment of these lesions often changes the post-operative protocol in addition to the surgical plan. MRI sensitivity for concomitant lesions is high, especially when evaluating for osteochondral lesions [41][42][43][44]. However, the utility in diagnosing symptomatic lateral ankle instability is limited because it is a static study.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Although MRI may identify associated pathology, such as osteochondral lesions, peroneal tendon tears, and loose bodies, the sensitivity of identifying such is still lower than with arthroscopy. 36,37 Clinicians should be systematic in evaluating the ankle joint during arthroscopy so as not to overlook these subtle concomitant injuries.…”
Section: Patient Evaluationmentioning
confidence: 99%
“…Dynamic ultrasound also can be helpful. 5,6,7,11,16 TREATMENT Without any evidence of acute rupture, most agree on conservative management, although the duration varies among authors ranging from 2--6 months. 1--5,6,7,14,15,22 Conservative management consists of anti-inflammatory medication, bracing, orthotics, and physical therapy.…”
Section: Diagnosismentioning
confidence: 99%
“…16 Recent studies have shown that MRI remains the most reliable objective measure of tears, although inaccuracies still remain. 6,7,13 Dynamic ultrasound also has proven to be a useful tool. 16 Initial conservative treatment is recommended unless an acute tear or rupture is evident.…”
mentioning
confidence: 99%
See 1 more Smart Citation